0784 Associations Of Sleep Regularity And Chronotype With Hypertension Among African Americans In The Jackson Heart Sleep Study. (27th May 2020) - Johnson, D A; Guo, N; Redline, S
Abstract: Introduction: Emerging evidence suggests that disparities in sleep regularity, a marker of circadian disruption, contributes to hypertension disparities; however, data among African Americans are limited. We examined associations of sleep regularity and chronotype with hypertension among African Americans in the Jackson Heart Sleep Study (JHSS). Methods: Participants underwent 7-day actigraphy, completed questionnaires, and had seated blood pressure (BP) measured as part of the JHSS (2012 - 2016). Sleep regularity was defined as the standard deviation (SD) of actigraphy-measured sleep onset timing or sleep duration. Chronotype was assessed by the Morningness-Eveningness Questionnaire. Prevalent hypertension was defined as either a systolic BP ≥ 130 mmHg or diastolic BP ≥ 80mmHg, antihypertensive medication use, or self-report of diagnosed hypertension. Multivariable logistic regression models were fit to estimate the prevalence odds ratio (OR) and 95% confidence intervals for the associations of hypertension with sleep regularity measures (SD of sleep onset timing and sleep duration) and chronotype adjusted for covariates. Results: Participants (n=830) on average were 63.4 years (SD:10.7), mostly female (66.3%) and hypertensive (85.8%). Compared to individuals with sleep onset SD < 30 minutes, higher adjusted odds of hypertension was observed with increasing variability: OR:1.87 (CI:0.99-3.56); OR:2.16 (1.06-4.39), and OR:2.41 (1.12-5.20), for SD > 30 & ≤ 60, > 60 & ≤ 90 and > 90 minutes, respectively. Among non-shift workers, definite morning and evening types compared to intermediates had higher adjusted odds of hypertension, OR:1.71 (1.04-2.83) and OR:2.56 (1.12-5.84), respectively. There were no observed associations for the SD of sleep duration with hypertension. Conclusion: Increased sleep onset variability and extreme chronotypes were associated with prevalent hypertension, supporting interventions targeting sleep hygiene recommendations promoting regular sleep. Future research is needed to understand sleep patterns and risk of cardiovascular disease according to chronotype. Support: NHLBI K01HL138211 and HL110068-03S1